Nature, the Picturesque and the Sublime in Mary Wollstonecraft Shelley’s Travel Narratives - Braida, Antonella (Hungarian Journal of English and American Studies, 2021)
The article explores Mary Shelley’s approach to the sublime and the picturesque in her two travel narratives, History of a Six Weeks’ Tour and Rambles in Germany and Italy. These two accounts of her travels through France, Switzerland, Italy, and Germany reveal her debt to a variety of contemporary sources aimed at exploring the nature of a sublime or picturesque experience. The analysis illustrates the complexity of Mary Shelley’s approach: while moving beyond the “egotistical sublime” typified by some key passages from William Wordsworth’s Prelude, her travel narratives reveal a variety of approaches to nature and the landscape, aimed at bridging present and past, personal experience and recent historical events.  Thus, while in History, the experience of the landscape offers a way out of the suffering caused by the Napoleonic Wars, in Rambles, Mary Shelley turns to poetry and painting, this way transforming the eighteenth-century aesthetic appreciation of landscape based on the pictorial categories of the sublime and the beautiful, and embracing a modern, cultivated sensibility nourished by guidebooks and art history manuals.  (AB)